Effect of vestibular stimulation using a rotatory chair in human rest/activity rhythm. (2nd August 2020) - Pasquier, Florane; Bessot, Nicolas; Martin, Tristan; Gauthier, Antoine; Bulla, Jan; Denise, Pierre; Quarck, Gaëlle
ABSTRACT: The vestibular system is responsible for sensing every angular and linear head acceleration, mainly during periods of motor activity. Previous animal and human experiments have shown biological rhythm disruptions in small rodents exposed to a hypergravity environment, but also in patients with bilateral vestibular loss compared to a control population. This raised the hypothesis of the vestibular afferent influence on circadian rhythm synchronization. The present study aimed to test the impact of vestibular stimulation induced by a rotatory chair on the rest/activity rhythm in human subjects. Thirty-four healthy adults underwent both sham (SHAM) and vestibular stimulation (STIM) sessions scheduled at 18:00 h. An off-vertical axis rotation on a rotatory chair was used to ecologically stimulate the vestibular system by head accelerations. The rest/activity rhythm was continuously registered by actigraphy. The recording started one week before the first session (BASELINE), continued in the week between the two sessions and one week after the second session. Vestibular stimulation caused a significant decrease in the average activity level in the evening following the vestibular stimulation. A significant phase advance in the rest/activity rhythm occurred two days after the 18:00 h vestibular stimulation session. Moreover, the level of motion sickness symptoms increased significantly after vestibular stimulation. The present study confirms previous results on the effect of vestibular stimulation and the role of vestibular afferents on circadian biological rhythmicity. Our results support the hypothesis of the implication of vestibular afferents as non-photic stimuli acting on circadian rhythms.